2014
DOI: 10.11144/javeriana.upsy13-3.cdaf
|View full text |Cite
|
Sign up to set email alerts
|

Características y desarrollo del acogimiento familiar en dos países con fuerte tradición de acogimiento residencial: España y Portugal

Abstract: r e S u M e n Los procesos de acogimiento familiar que se producen en cada país dependen de factores históricos y culturales que dan lugar a grandes diferencias internacionales. A pesar de que las comparativas internacionales ofrecen un medio de intercambio de experiencias, lo que permite el aprendizaje mutuo y la transferencia de buenas prácticas, a menudo encontramos enormes barreras para su realización debido, entre otros factores, al limitado acceso a los datos sobre la práctica de la protección infantil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
2
0
4
Order By: Relevance
“…Entre as diferenças mais signifi cativas destaca-se a maior expressão da colocação em acolhimento familiar no caso espanhol e o predomínio do acolhimento em instituição em Portugal; a importância da família alargada e com a maior idade no início do acolhimento das crianças e jovens em Espanha; o perfi l dos acolhedores, com idades mais avançadas, um baixo nível educativo e levando a cabo acolhimentos múltiplos, em Portugal (López, Delgado, Carvalho, & Del Valle, 2014).…”
Section: O Acolhimento Familiar Nos Sistemas De Proteção Dos Países Iunclassified
“…Entre as diferenças mais signifi cativas destaca-se a maior expressão da colocação em acolhimento familiar no caso espanhol e o predomínio do acolhimento em instituição em Portugal; a importância da família alargada e com a maior idade no início do acolhimento das crianças e jovens em Espanha; o perfi l dos acolhedores, com idades mais avançadas, um baixo nível educativo e levando a cabo acolhimentos múltiplos, em Portugal (López, Delgado, Carvalho, & Del Valle, 2014).…”
Section: O Acolhimento Familiar Nos Sistemas De Proteção Dos Países Iunclassified
“…El comportamiento violento comienza a surgir durante esta etapa, especialmente cuando la situación familiar (e.g., maltrato) no permite a los jóvenes crecer apropiadamente y el comportamiento agresivo aparece fuera del hogar familiar, en residencias o centros de acogida (Aroca, Bellver, & Alba, 2013; Bernedo, Salas, Fuentes, & García-Martín, 2014). En España, cuando el adolescente no vive en el hogar familiar, es más probable que se aloje en un centro residencial y no en un hogar de acogida (López, Delgado, Carvalho, & Del Valle, 2014). Crecer en este tipo de entorno tiene un impacto negativo en su desarrollo, que incluye problemas emocionales y conductuales.…”
Section: Conducta Violenta Victimización Autoestima Y Actividad Físic...unclassified
“…Violent behaviour begins to appear during this stage, especially when the family situation (e.g., mistreatment) does not allow children to flourish properly and aggressive behaviour emerges outside of the family home, such as in residences or refuges (Aroca, Bellver, & Alba, 2013; Bernedo, Salas, Fuentes, & García-Martín, 2014). In Spain, adolescents are more likely to be brought up in residences than refuges when they do not reside in the family home (López, Delgado, Carvalho, & Del Valle, 2014). This type of upbringing has negative impacts on their development, including emotional and behavioural problems.…”
mentioning
confidence: 99%
“…Additionally, as a result of the in-depth literature review that has been carried out, it is concluded that there is a lack of published instruments designed to collect sociodemographic data that have proven to be valid and effective in the child and adolescent population, and even less so in minors with such specific experiences as those involved in the child welfare system. These forms are often developed ad hoc for a particular research and sample (see [ 8 ]). They do not focus on exploring specific aspects of this group (e.g., their history in the child welfare system) that may be of great importance when preparing interventions or explaining other aspects of their psychophysical development.…”
Section: Introductionmentioning
confidence: 99%